2017
DOI: 10.1007/s12011-017-1228-3
|View full text |Cite
|
Sign up to set email alerts
|

The Divalent Elements Changes in Early Stages of Chronic Kidney Disease

Abstract: As the glomerular filtration rate (GFR) decreases, it can cause imbalance in some divalent elements. These imbalances can cause increased oxidative stress in patients with renal impairment. The aim of present study was to investigate the changes of these divalent elements with CKD progression. One hundred and ninety-four patients with chronic kidney diseases (CKD) were divided into five stages, stage 1, 2, 3a, 3b, 4, and were recruited into this study. The divalent elements, calcium, magnesium, phosphorus, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…As CKD progresses, GFR decreases, leading to an imbalance of certain trace elements, and higher CKD stages are associated with increased levels of Cu and decreased levels of Zn ( 153 ). This suggests the Cu/Zn ratio could be used as a marker for early and late detection of renal failure ( 154 ).…”
Section: Discussionmentioning
confidence: 99%
“…As CKD progresses, GFR decreases, leading to an imbalance of certain trace elements, and higher CKD stages are associated with increased levels of Cu and decreased levels of Zn ( 153 ). This suggests the Cu/Zn ratio could be used as a marker for early and late detection of renal failure ( 154 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is essential for the human body and is involved in many catalytic, structural, and regulatory activities, including the replication of DNA, energy metabolism, maintenance of protein structure, body growth and development 39 , 40 . Multiple epidemiological studies have found that Zn deficiency may have harmful impacts on human health, such as inducing CKD 33 , 34 . However, in our study, the highest exposure to Zn was associated with an increased risk of hazardous renal performance, which provides potential evidence for the U-shaped association between Zn and renal health.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, zinc de ciency has been found to speci cally upregulate the expression of nicotinamide adenine dinucleotide phosphate oxidase 2 in renal tubular epithelial cells, promote oxidative stress, and cause kidney damage [23]. In CKD patients, the serum zinc was decreased, which was signi cantly negatively correlated with the serum phosphorus level, positively correlated with the serum total protein, albumin and serum calcium levels [24]. Correcting the low level serum zinc could help to delay the progression of CKD and prevent its complications [25].…”
Section: Discussionmentioning
confidence: 99%